Does Balancing Fund Affect Economic Growth and Poverty Level in Central Java? - Magdalena Nany; Trisni Suryarini (Jurnal Kajian Akuntansi, 2022)
AbstractFiscal federalism copes with the division of governmental function and financial relations among levels of authorities. The objective of this research was to give empirical evidence about the effects of Local Own-Source Revenue (PAD), Revenue Sharing Fund (DBH), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Local Expenditure (BD) on economic growth and poverty level. The data of this study were sourced from secondary data. The data collection method used was mechanical observation technique. Panel data from 35 districts and municipalities in Central Java province throughout 2009-2018 were analyzed by multiple regression analysis. This study concludes that balancing funds have an affect on increasing economic growth (except DBH) and reducing poverty levels even though not as effective as PAD. In contrast, local expenditure does not have an affect on increasing economic growth and reducing poverty levels. This study supports the fiscal federalism theory, that the allocation of sources can be accomplished effectively by states and local governments. Balancing funds have an affect on increasing economic growth and decreasing poverty levels.Keywords: Growth; Local expenditure; Local revenue; Poverty Abstrak Federalisme fiskal berkaitan dengan pembagian fungsi pemerintahan dan hubungan keuangan di antara tingkat-tingkat pemerintahan. Studi ini bertujuan untuk memperoleh bukti empiris tentang dampak Pendapatan Asli Daerah (PAD), Dana Bagi Hasil (DBH), Dana Alokasi Umum (DAU), Dana Alokasi Khusus (DAK), dan Belanja Daerah (BD). pada pertumbuhan ekonomi dan tingkat kemiskinan. Data penelitian ini bersumber dari data sekunder yang berasal dari Biro Pusat Statitstik Provinsi Jawa Tengah. Teknik pengumpulan data yang digunakan adalah teknik observasi mekanik. Data panel dari 35 kabupaten dan kota di Provinsi Jawa Tengah sepanjang tahun 2009-2018 dianalisis dengan analisis regresi berganda. Studi ini menyimpulkan bahwa dana perimbangan berdampak pada peningkatan pertumbuhan ekonomi (kecuali DBH) dan penurunan tingkat kemiskinan meskipun tidak seefektif PAD. Sebaliknya, belanja daerah tidak berdampak pada peningkatan pertumbuhan ekonomi dan penurunan tingkat kemiskinan. Studi ini mendukung teori federalisme fiskal, bahwa alokasi sumber dapat dilakukan secara efektif oleh pemerintah pusat dan pemerintah daerah. Dana perimbangan berdampak pada peningkatan pertumbuhan ekonomi dan penurunan tingkat kemiskina.Katakunci: Belanja daerah; Kemiskinan; Pendapatan daerah; Pertumbuhan